2019
DOI: 10.1002/tl.20365
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Capital, Positive Psychology, and Active Learning and Mindful Teaching

Abstract: This chapter shows how freshmen students entering at the university have to cope with a new life and face a variety of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
9
0
8
Order By: Relevance
“…The previous results showed that there were statistically significant differences between the mean scores of the experimental and control groups in the postmeasurement of the tendency towards intellectual extremism scale and its components, in favour of the experimental group. This result is in general consistent with the findings of various previous research, confirming that dialogue and positive thinking help individuals reflect on their thinking, review their reactions and evaluate the situations they are going through and therefore it is a good way to get rid of the negative irrational thoughts that accompany intellectual extremism (Gendron et al, 2016;Gibbons, 2012;Warren et al, 2013). Also, such training urges the individual to participate constructively in any psychological training programmes for his psychological problems and makes him feel more selfresponsible for his behaviour and his way of thinking.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The previous results showed that there were statistically significant differences between the mean scores of the experimental and control groups in the postmeasurement of the tendency towards intellectual extremism scale and its components, in favour of the experimental group. This result is in general consistent with the findings of various previous research, confirming that dialogue and positive thinking help individuals reflect on their thinking, review their reactions and evaluate the situations they are going through and therefore it is a good way to get rid of the negative irrational thoughts that accompany intellectual extremism (Gendron et al, 2016;Gibbons, 2012;Warren et al, 2013). Also, such training urges the individual to participate constructively in any psychological training programmes for his psychological problems and makes him feel more selfresponsible for his behaviour and his way of thinking.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Bakkar (2007) concluded that more than 50% of university students show negative thinking. Among the studies that show the importance of training in positive thinking to reduce the negative effects of irrational thoughts are the most important sources of intellectual extremism (Gendron et al, 2016;Gibbons, 2012;Warren et al, 2013). These studies confirmed that dialogue and positive thinking help individuals reflect on their thinking, review their reactions and evaluate the situations they are going through, and thus it is a good way to get rid of the negative, irrational thoughts that accompany intellectual extremism.…”
Section: Introductionmentioning
confidence: 85%
“…Discriminant validity is used by cross loading factor method and Fornell and Larker method. In the second part analysis (the fit of the structural model) these criteria are used: Goodness of Fit (GOF) index, prediction power index Q 2 , T values, R Square or Criterion [54].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, two different approaches both indicated that the PECQ has acceptable reliability and validity. The quality of the structural model was assessed with the prediction power index Q 2 . Positive values indicate that the observed values are well restored, suggesting that the quality of the structural model is good [66].…”
Section: The Fornell-larker Methodsmentioning
confidence: 99%
See 1 more Smart Citation